Acceleration of a high-current proton beam in a linear induction accelerator at its compensation by electron beams - Fedorovskaya, O.V.; Maslov, V.I.; Onishchenko, I.N. (Вопросы атомной науки и техники, 2022)
The dynamics of a high-current proton beam in the cusp magnetic field and in the uniform magnetic field of the drift region in the presence of an accelerating field in the cusp region and of two types of compensating electron beams (before and after the cusp) has been studied. It is shown that for the taken beam parameters and magnetic field it is impossible to accelerate a proton beam of the density higher than 10¹² cm⁻³ with maintaining its initial transverse size and monoenergeticity.